Rancang Bangun Sistem Informasi Produk Unggulan Desa Berbasis Web - Raden Erwin Gunadhi Rahayu; Muhamad Resa Agustina (Jurnal Algoritma, 2022)
Cintakarya Village, Samarang subdistrict, has superior products such as vegetables, fruits and Muslim caps which have been sold outside the island. These products are sold by village-owned enterprises (BUMDes) which were formed to help the community's needs. One of the community service programs is managed by village-owned enterprises (BUMDes). This study aims to design and build a web-based village superior product data system in Cintakarya Village, a case study in the BUMDes of Cintakarya Village to make it easier for the community to obtain product information in the village and buy products available in Cintakarya Village. In this research the author uses the Rational Unified Process (RUP) method with 4 stages, namely Inception, Elaboration, Construction, Transition by applying the Unified Modeling Language (UML) modeling. The results of this research are Design and Development of a Web-Based Village Product Information System in Cintakarya village.